Activity Hysteresis during Cyclic Temperature-Programmed Reactions in the Partial Oxidation of Acrolein to Acrylic Acid - Knoche, Stefan; Heid, Maurice; Gora, Niklas; Ohlig, Dominik; Drochner, Alfons; Vogel, Herbert; Etzold, Bastian J.M. (Chemical Engineering & Technology, 2017)
Oxidation of acrolein to acrylic acid on a Mo/V/W mixed oxide catalyst was studied by transient (cyclic temperature-programmed (TP)) as well as steady-state methods. TP reactions (TPReactions) exhibit an activity hysteresis of the catalyst with respect to temperature. As a result of the steady-state measurements, the activity hysteresis is not related to multiple steady states and is exclusively a transient phenomenon. Generally, the dynamics of bulk oxygen plays a key role leading to a reversible oxidation/reduction of the catalyst surface which influences the activity. This means the bulk acts as oxygen buffer. In this context, a reaction model, which involves the participation of bulk oxygen, was deduced and verified by modeling.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Acrolein; Acrylic acid; Activity hysteresis; Bulk oxygen; Mixed oxide catalysts